Mississippi grind [videorecording (DVD)] - Boden, Anna; Fleck, Ryan, 1976-; Miller, Sienna, 1981-; Reynolds, Ryan; Mendelsohn, Ben; Woodard, Alfre, 1953- (Lionsgate, 2015)
Down on his luck gambler Garry and his hot streak buddy Curtis hit the road for New Orleans, hunting the big payday. On riverboats and racetracks they chase women and thrills before risking it all in the wager of their lives.